Green Choices in E-Commerce: Understanding Consumer Willingness to Pay for Eco-Friendly Packaging - Hapsari, Nurul Retno; Mu’afi, Muhammad Irfan; Nurchaya, Mukti Ahmad (Jurnal AGRISEP, 2026)
This study examines consumer behavior toward adopting eco-friendly packaging in Indonesia’s e-commerce sector, contributing to the broader discourse on sustainable consumption in Indonesia. It analyzes the factors influencing consumers’ willingness to pay for eco-friendly packaging using the Sustainability Theory of Planned Behavior (STPB). The study is driven by growing environmental concerns associated with e-commerce packaging waste, particularly in emerging markets such as Indonesia, where sustainability practices are still developing. Data were collected from 236 active online shoppers through purposive sampling, and structural equation modelling (SEM) was employed to analyze the relationships among key variables. The results demonstrate the significant influence of environmental concerns on consumer attitudes and the crucial role of behavioral intention in predicting willingness to pay for eco-friendly packaging. The findings further indicate that moral and environmental values play a more prominent role than economic considerations in shaping consumer behavior. These insights underscore the importance of public awareness campaigns, improved accessibility to eco-friendly packaging, and supportive government policies. By integrating sustainability dimensions into consumer behavior models, this study advances the theoretical understanding of sustainable consumption in e-commerce and offers practical recommendations for promoting environmental responsibility in emerging markets.